Proposal of a new subfamily of Sciaridae (Diptera: Sciaridae), with description of one new species from South Korea - Shin, Seunggwan; Lee, Heungsik; Lee, Seunghwan (Zootaxa, 2019)
Here we propose a new monophyletic subfamily, the Chaetosciarinae, based on previous morphological cladistic and molecular phylogenetic studies. This new subfamily includes the genera Chaetosciara Frey, Mouffetina Frey, Schwenckfeldina Frey, and Scythropochroa Enderlein. We also provide a definition of the new subfamily Chaetosciarinae and describe common morphological key characters. Three Korean Chaetosciarinae species in three genera are reported, all of which are new to Korea and one (Scythropochroa pseudoquercicola sp. nov.) of which is new to science. A previous molecular phylogenetic study designated Scy. pseudoquercicola as an unidentified species. Our study provides examined species information for members of this new subfamily to accompany the GenBank accession numbers published by a previous molecular phylogenetic study. Furthermore, we present a multigene molecular phylogenetic analysis for the Chaetosciarinae.